Estudio de los factores de producción en el cultivo de palma aceitera para maximización de los rendimientos en el Ecuador. - Mayorga Franco, Marcelo Duberly (2022)
The present study entitled "Study of production factors in oil palm cultivation to maximize yields in Ecuador" had the objective of collaborating with oil palm producers from an agricultural point of view, in order to propose possible solutions applied to the management of the crop. The production factors are not implemented in a technical way from the time of planting to the harvest, being more noticeable in family farms, which leads to a reduction in the harvest, causing economic losses. Therefore, we recommend that field days, community liaison and theses be carried out to improve the subject as much as possible.